Perinatal factors related to pregnancy and childbirth satisfaction: a prospective cohort study. (3rd July 2021) - Lemmens, Stéphanie M. P.; van Montfort, Pim; Meertens, Linda J. E.; Spaanderman, Marc E. A.; Smits, Luc J. M.; de Vries, Raymond G.; Scheepers, Hubertina C. J.
Abstract: Background: Satisfaction of pregnancy and childbirth is an important quality measure of maternity care. Satisfaction questionnaires generally result in high scores. However, it has been argued that dissatisfaction relies on a different construct. In response to a worldwide call for obstetric care that is more woman-centered, we identified and described the contributors to suboptimal satisfaction with pregnancy and childbirth. Methods: A prospective subcohort of 739 women from a larger cohort (Expect Study I, n = 2614) received a pregnancy and childbirth satisfaction questionnaire. Scores were transformed to a binary outcome whereby a score <100 points corresponded with less satisfied women. We performed a multiple logistic regression analysis to define independent perinatal factors related to suboptimal satisfaction. Results: Decreased perceived personal well-being, antenatal anxiety, and obstetrician-led care during labor were all independently associated with suboptimal pregnancy and childbirth satisfaction. No difference in satisfaction was found between antenatal care led by a midwife or an obstetrician, but midwife-led antenatal care reduced the odds of suboptimal satisfaction compared to women who were transferred to an obstetrician in the antenatal period. Antenatal anxiety was experienced by 25% of all women and is associated with decreased satisfaction scores. Discussion: Screening and treatment of women suffering from anxiety might improve pregnancy and childbirth satisfaction, but further research is necessary. Women's birthing experience may improve by reducing unnecessary secondary obstetric care.